PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION DI KELAS III SD - Nurlev Avana; Subhanadri Subhanadri; Ambiyar Ambiyar; Ishak Aziz; Desmawati Desmawati (Jurnal Muara Pendidikan, 2023)
The problem in this study is that student learning outcomes in Mathematics for Class III SD Negeri 111/II Bukit Telago Pelepat are still relatively low, the interaction between educators and students has not been seen, and the learning process is teacher-centered or educator-centered. The purpose of this study was to describe the application of the Team Assisted Individualisation model in class III SD Negeri 111/II Bukit Telago Pelepat on learning processes and outcomes This research is a Classroom Action Research (CAR). The subjects of this study were Class III students of SD Negeri 111/II Bukit Telago Pelepat with a total of 15 students, this study consisted of 2 cycles, and each cycle was carried out through 4 stages, namely planning, observation, and reflection. And each cycle did two meetings. The results showed that using the Team Assisted Individualization model could improve third-grade mathematics' process and learning outcome at SD Negeri 111/II Bukit Telago Pelepat. This can be seen from the test results in the first cycle, only 7 or 46.66% of students who scored in the maximum completeness criteria were 62 and 8 or 53.33% had not reached the maximum completeness criteria. Student learning outcomes increased very well in cycle II. From 26.66% (initial observation), to 46.66% (cycle I) and 86.66% (cycle II) and the learning process of students in the first cycle of the first meeting was 68.33% and at the second meeting increased to 75, 00%, while in the second cycle of the first meeting 79.17% and at the second meeting it increased to 90.00% this has exceeded the predetermined category.